Experimental Validation of a Dynamic Model for Lightweight Robots. (28th March 2013) - Gasparetto, Alessandro; Moosavi, Amir Kiaeian; Boscariol, Paolo; Giovagnoni, Marco
Nowadays, one of the main topics in robotics research is dynamic performance improvement by means of a lightening of the overall system structure. The effective motion and control of these lightweight robotic systems occurs with the use of suitable motion planning and control process. In order to do so, model-based approaches can be adopted by exploiting accurate dynamic models that take into account the inertial and elastic terms that are usually neglected in a heavy rigid link configuration. In this paper, an effective method for modelling spatial lightweight industrial robots based on an Equivalent Rigid Link System approach is considered from an experimental validation perspective. A dynamic simulator implementing the formulation is used and an experimental test-bench is set-up. Experimental tests are carried out with a benchmark L-shape mechanism.